1978
DOI: 10.1126/science.715455
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin Is Associated with Overeating in Genetically Obese Mice ( ob / ob ) and Rats ( fa / fa )

Abstract: Small doses of the opiate antagonist naloxone selectively abolished overeating in genetically obese mice (ob/ob) and rats (fa/fa). Elevated concentrations of the naturally occurring opiate beta-endorphin were found in the pituitaries of both obese species and in the blood plasma of the obese rats. Brain levels of beta-endorphin and Leu-enkephalin were unchanged. These data suggest that excess pituitary beta-endorphin may play a role in the development of the overeating and obesity syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
3

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(83 citation statements)
references
References 15 publications
1
79
3
Order By: Relevance
“…Pituitary f-endorphin is also elevated in ob/ob mice and obese (Zucker) rats (6). Furthermore, hypothalamic injections of f-endorphin result in overeating by nonobese rats (7,8), whereas injections of naloxone, an opiate antagonist, result in decreased food intake in rats (9) and mice (6,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pituitary f-endorphin is also elevated in ob/ob mice and obese (Zucker) rats (6). Furthermore, hypothalamic injections of f-endorphin result in overeating by nonobese rats (7,8), whereas injections of naloxone, an opiate antagonist, result in decreased food intake in rats (9) and mice (6,10).…”
mentioning
confidence: 99%
“…The latter effect has been found to be more pronounced for ob/ob mice than for ob/? heterozygous controls (6). These data have led to recent speculation that the obesity of ob/ob mice is caused by abnormal opioid metabolism and that f3-endorphin may play a role in the regulation of food intake through interactions with central, gastrointestinal, or pancreatic opiate receptors (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…How ingestion of palatable food is regulated is of great interest to those studying ingestive behavior as well as those studying basic mechanisms of motivation and reward. One of the first neurochemical systems implicated in the hedonics of feeding and obesity was the endogenous opioid system (Belluzzi and Stein, 1977;Mandenoff, et al, 1982;Margules, et al, 1978). In general, opioid antagonists are anorexigenic while opioid agonists are orexigenic [reviewed in (Bodnar, 2004;Glass, et al, 1999)].…”
mentioning
confidence: 99%
“…To date, the direct effects of endogenous opioids on myocardial contractility have not been investigated. Thus, the purpose of the present study was to determine if enkephalins ([Met] (Margules et al, 1978), have been shown to have a reduced inotropic response to secretin and (± )-isoprenaline, compared to lean controls (Chatelain et al, 1981;Robberecht et al, 1983).…”
Section: Introductionmentioning
confidence: 99%